الضغوط المهنية وعلاقتها بالأداء الوظيفي (دراسة ميدانية لدى الموظفين في مكتبة الأسد الوطنية بدمشق) - نعامة, سليم; علي, أنور (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى معرفة الفروق بين أفراد عينة البحث على مقياس مصادر الضغوط المهنية ومقياس الأداء الوظيفي المستخدم في هذا البحث استناداً إلى مجموعة من المتغيرات (عدد سنوات الخبرة، المؤهل التعليمي). وتكونت عينة الدراسة من (120) عاملاً وعاملة من موظفي مكتبة الأسد الوطنية، وتمثل هذه العينة ما نسبته (30%) من مجتمع البحث الأصلي. واعتمدت الدراسة على أداتي مقياس الضغوط المهنية، ومقياس الأداء الوظيفي. وتوصل البحث إلى النتائج الآتية: - أكثر مصادر الضغوط المهنية شيوعاً هو المصدر السادس "الضغوط الناتجة من المردود المادي". - توجد علاقة ارتباطية ذات دلالة إحصائية بين مصادر الضغوط المهنية والأداء الوظيفي تبعاً لمتغيرات البحث (سنوات الخبرة، المؤهل التعليمي). وتوصل البحث إلى عدد من المقترحات منها: تفعيل الانضباط الإداري الذي يشمل الالتزام بمواعيد العمل والمحافظة على الممتلكات العامة والكياسة في التعامل مع المراجعين. العمل على تخفيف ضغوط العمل للعاملين في المكتبات الأكاديمية بتفعيل الاتصال الإنساني بين المراجعين المستفيدين وبين العاملين. This research aims to identify the differences between the members of the research sample on a scale of occupational stress sources and the job performance measure used based on a set of variables (years of experience, educational qualifications). The study sample consists of (120) workers and staff in the Al-Assad National Library, representing 30% of the original search. This study relies on instruments measuring occupational pressures and job performance. This research obtains the following results: - the most common source of occupational stress is the sixth source representing "the pressures resulting from financial income." - There is a statistically significant correlation between the sources of occupational stress and job performance in terms of the research variables (years of experience, educational qualification). This research has put forward a number of proposals, including: 1. Activating administrative discipline, which includes observing work schedules and maintaining public properties and courtesy in dealing with customers. 2. Working to alleviate work pressures for those working in academic libraries by activating human communication between beneficiaries and employees.